The use of antimicrobial drugs in preterm newborn: the experience of creating the formulary - M. A. Ivzhits; S. K. Zyryanov; E. A. Ushkalova; G. V. Rodoman; S. I. Zhogin; O. A. Babak; O. I. Milyeva; S. V. Dumova (Качественная клиническая практика, 2018)
A serious problem of treatment of infectious disease in preterm infants is the lack of sufficient information on pharmacokinetics of antibiotics in this group of patients. This is due to the insufficient number of clinical trials with premature babies, so in practice is difficult for doctor to choose appropriate antibiotic dose and frequency of dosing him. We have summed up the experience of the American pediatric form NEOFAX, British pediatric form, some clinical trials results and selected the optimal dosing regimen of antibacterial drugs based on gestational and post-conceptual age. This will contribute to safety and efficiency in the treatment of infectious diseases in premature infants caused primarily problematic nosocomial pathogens, such as Acinetobacter spp., Klebsiella pneumonia, Pseudomonas aeruginosa, MRSA, and reduce the risk of adverse drug reactions.